Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1999
DOI: 10.1016/s0009-9236(99)70057-3
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic and coronary effects of intravenous eletriptan, a 5HT -receptor agonist

Abstract: Eletriptan, a 5HT1B/1D-agonist effective in migraine, causes no significant coronary artery constriction in patients without significant obstructive coronary artery disease. This finding may reflect a relative selectivity for the 5HT1D-receptor subtype.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 14 publications
2
32
0
Order By: Relevance
“…Eletriptan was infused at 3.33 g/kg/min (which resulted in a mean free C max equivalent to that observed after an oral dose of 40 mg) and it produced no significant changes in the mean proximal, middle, or distal coronary artery diameters. 47 However, one of the 10 patients investigated exhibited a segmental constriction of the proximal right coronary artery that may have been catheter-induced 47 or perhaps caused by the drug. In contrast, IV infusion of sumatriptan (total dose of 48 g/kg) reduced the coronary artery diameter significantly by 13%.…”
Section: Results Basic Contractile Propertiesmentioning
confidence: 99%
“…Eletriptan was infused at 3.33 g/kg/min (which resulted in a mean free C max equivalent to that observed after an oral dose of 40 mg) and it produced no significant changes in the mean proximal, middle, or distal coronary artery diameters. 47 However, one of the 10 patients investigated exhibited a segmental constriction of the proximal right coronary artery that may have been catheter-induced 47 or perhaps caused by the drug. In contrast, IV infusion of sumatriptan (total dose of 48 g/kg) reduced the coronary artery diameter significantly by 13%.…”
Section: Results Basic Contractile Propertiesmentioning
confidence: 99%
“…40 ) out significant obstructive CAD who were undergoing cardiac catheterization for investigation of chest pain when they received intravenous eletriptan, which was infused to achieve plasma levels similar to those observed with a 40-mg oral dose. 41 Other studies of subcutaneous sumatriptan have reported a reduction in mean absolute coronary artery diameter of between 12.9% and 17% in patients undergoing diagnostic cardiac catheterization. There were no clinical symptoms suggestive of angina or electrocardiographic evidence of myocardial ischemia related to the decrease in coronary artery diameter.…”
Section: Angiographic and Pet Studiesmentioning
confidence: 97%
“…The occurrence of myocardial infarction attributable to eletriptan overdose in a patient without coronary artery disease has been recently reported but, to best of our knowledge, it is a unique case. Notably, eletriptan has been demonstrated in animals to induce coronary constriction at four times higher dose than sumatriptan [Muir et al 1999]. Therefore, it represents the triptan of choice in patients with cardiovascular risk factors, without coronary artery disease.…”
Section: Tolerability and Safetymentioning
confidence: 99%